Analysis of Institutional Quality Impact on Foreign Direct Investment: A Case Study of Countries in America, Asia, and Europe - Suripto Suripto; Galih Dwi Prihandika; Rifki Khoirudin (AIBPM Publisher, 2025)
Countries worldwide are making development efforts to improve the welfare of their people. Significant investment is needed to accelerate economic growth. This study examines the impact of institutional, macroeconomic, and social quality on foreign direct investment (FDI). The method used is the two-step Generalized Method of Moments (GMM). The study's subjects include 94 countries worldwide located in America (26 countries), Asia (33 countries), and Europe (35 countries) over the period 2002 – 2021. The secondary data collection used in this study is sourced from the World Development Indicators (WDI) and World Governance Indicators (WGI). The results of the study show that, simultaneously, all independent variables affect FDI in all models. Meanwhile, the results indicate that institutional quality is more effective in Europe than in America and Asia. Additionally, FDI in the previous period significantly impacts FDI in all models. This study also concludes that inflation and labor force have consistent significance in almost all models, indicating that these variables play an important role in FDI.